Chronic air pollution and health burden in Dhaka city. Issue 2 (6th August 2020) - Siddiqui, Shafayet Ahmed; Jakaria, Md; Amin, Mohammad Nurul; Al Mahmud, Abdullah; Gozal, David
Air quality is usually evaluated by the concentrations of particulate matter and gaseous substances that are present in the air we breathe. Thousands of pollutants are responsible for environmental air pollution, with particulate matter with a 50% cut-off aerodynamic diameter of 2.5 µm (PM2.5 ), PM10, carbon monoxide, ozone, sulfur dioxide and NOx being those most frequently evaluated. In developing countries such as Bangladesh, awareness of air pollution is virtually non-existent and, most of the time, ignored even when air quality becomes unbearable to most citizens. Among the sources of particulate matter in Dhaka, the large metropolis that serves as the capital city of Bangladesh, road dust, textile and dying businesses, tanneries, chemical and cement factories, and brick kilns emerge as the most polluting offenders. Substantial evidence has shown that PM2.5 is independently implicated in cardiovascular and respiratory diseases, and cancer, in light of its ability to reach terminal bronchioles and alveolar structures, and even reach the bloodstream [1]. Air pollution levels in developing countries such as Bangladesh with a relatively young population pose an inordinate health risk for many years to come unless significant environmental control measures are effectively undertaken https://bit.ly/3bvzesx